Kodifikacija (splošnega) upravnega postopka kot mehanizem dobrega upravljanja: primerjava ureditev v Sloveniji, Avstriji in na Hrvaškem - Babšek, Matej (Javna uprava, 2021)
Although the administrative procedure in Slovenia focuses only on issuing specific and individual administrative acts and thus largely serves as a procedural tool for individuals to protect their rights in relation to authorities, convergence processes require that its role and codification in the General Administrative Procedure Act (GAPA) are understood more broadly, namely in the context of good governance. With the aim to evaluate the current codification of administrative procedure in Slovenia, the author compares its basic functions in the context of good governance with regulations in the neighbouring countries of Austria and Croatia. The results suggest that the Slovenian codification of administrative procedure as a mechanism of the rule of law and thus of the protection of human rights and guarantees of the parties in the procedure is appropriate. However, when considered as a tool for broader public governance in administrative processes that pursue the integral set of principles of good governance and the related effective implementation of public policies, a number of shortcomings have been detected. Thus, the Slovenian codification does not use its potential for being a mechanism for reform and modernisation of public administration.
Keywords: administrative procedure; administrative reforms; Austria; Avstrija; codification; comparative administrative procedural law; Croatia; dobro upravljanje; good administration; good governance; Hrvaška; javna uprava; Slovenia; Slovenija; upravne reforme; upravni postopek; upravno pravo